Dynamic states of the DNA repair enzyme AlkB regulate product release. - Bleijlevens, B; Shivarattan, T; Flashman, E; Yang, Y; Simpson, P; Koivisto, P; Sedgwick, B; Schofield, C; Matthews, S (2008)
The 2-oxoglutarate (2OG)- and Fe(2+)-dependent dioxygenase AlkB couples the demethylation of modified DNA to the decarboxylation of 2OG. Extensive crystallographic analyses have shown no evidence of significant structural differences between complexes binding either 2OG or succinate. By using nuclear magnetic resonance spectroscopy, we have shown that the AlkB-succinate and AlkB-2OG complexes have significantly different dynamic properties in solution. 2OG makes the necessary contacts between the metal site and the large beta-sheet to maintain a fully folded conformation. Oxidative decarboxylation of 2OG to succinate leads to weakening of a main contact with the large beta-sheet, resulting in an enhanced dynamic state. These conformational fluctuations allow for the replacement of succinate in the central core of the protein and probably contribute to the effective release of unmethylated DNA. We also propose that the inherent dynamics of the co-product complex and the subsequent increased molecular ordering of the co-substrate complex have a role in DNA damage recognition.